DESIGNING ENGLISH READING TEXT BASED ON “ULOS BINTANG MARATUR" BATAKNESE FOLKLORE - Evi Novalin Bako; Tunsri Keumala; Yeni Leoni; Veranti Serena; Elda Setiani; Yenita Br Sembiring (BAHAS, 2022)
Abstract  Ulos Bintang Maratur is drenched in love, warmth, protection, and respect. This research aims: first, to develop Batak folklore. Secondly, to find out the influence of Batak folklore on reading comprehension and more knowledge of SMK Telkom-2 Medan community and ethnicity about Batak Folklore "Ulos Bintang Maratur" in Huta. This research describes the traditional tribes of the Batak community which includes the types of ulos and their history 1) the types of ulos and their history, one of which is Ulos Bintang Maratur, 2) to find out the Toba Batak tribe who make ulos as symbolic in every event, and finally this research aims to increase interest in reading and knowing the folklore of the Batak Ulos Bintang Maratur for students of SMK Telkom 2 Medan.  This type of research is descriptive qualitative obtained in writing to describe the moral values and character building contained in the depiction of traditional tribal tales of the Batak people. Data collection is done by reading the story text and describing the traditional tribes of the Batak people about "Ulos Bintng Maratur". From the research, it can be concluded that Batak folklore and the meaning of ulos Bintang Maratur can increase people's interest in reading and can be a motivation for every community, especially the Toba Batak ethnicity. The findings obtained by researchers are that they understand more about Batak customs, especially in the function of Ulos Bintang Maratur where parents are highly respected by their children, because the struggle of Batak parents for their children is extraordinary. As children, we must respect our parents. So when their children are successful they (parents) hold events in the village such as giving appreciation to Ulos Bintang Maratur as proof that their struggle is not for their children so that success will come to their children.Keywords : Batak Folklore, Respect, Reading Comprehension   Abstrak  Ulos Bintang Maratur penuh dengan cinta, kehangatan, perlindungan, dan rasa hormat. Penelitian ini bertujuan: pertama, untuk mengembangkan Cerita Rakyat Batak. Kedua, untuk mengetahui pengaruh cerita Rakyat Batak terhadap pemahaman membaca dan pengetahuan lebih lanjut dari masyarakat. Penelitian ini mendeskripsikan tentang suku adat masyarakat Batak yang meliputi jenis-jenis ulos dan sejarahnya 1) Jenis-jenis ulos dan sejarahnya, salah satunya Ulos Bintang Maratur, 2) Untuk mengetahui suku Batak Toba yang menjadikan ulos sebagai simbolis dalam setiap acara, dan yang terakhir penelitian ini bertujuan untuk meningkatkan minat baca dan untuk mengetahui seberapa paham mereka tentang cerita rakyat Batak Ulos Bintang Maratur pada siswa-siswi SMK Telkom 2 Medan.  Jenis penelitian ini adalah deskriptif kualitatif yang diperoleh secara tertulis untuk mendeskripsikan nilai-nilai moral dan pendidikan karakter yang terkandung dalam penggambaran cerita rakyat suku Batak. Pengumpulan data dilakukan dengan cara membaca teks cerita dan mendeskripsikan cerita suku tradisional masyarakat Batak tentang "Ulos Bintang Maratur". Dari hasil penelitian dapat disimpulkan bahwa cerita rakyat Batak dan makna ulos Bintang Maratur dapat meningkatkan minat baca masyarakat dan dapat menjadi motivasi bagi setiap masyarakat khususnya etnis Batak Toba. Temuan yang didapatkan oleh peneliti adalah lebih memahami tentang adat istiadat Batak khususnya dalam fungsi Ulos Bintang Maratur dimana orang tua sangat dihormati oleh anaknya, karena perjuangan orang tua Batak untuk anaknya sangat luar biasa. Sebagai anak, kita harus menghormati orang tua. Maka ketika anaknya sukses mereka (orang tua) mengadakan acara di kampung seperti memberikan penghargaan Ulos Bintang Maratur sebagai bukti bahwa perjuangan mereka tidak sia-sia untuk anaknya, sehingga kesuksesan itu datang kepada anak mereka. Kata kunci : Cerita Rakyat Batak, Rasa Hormat,Pemahaman Membaca